Prevalence and risk factor for obesity in urban and rural school going children of Karad taluka, Maharashtra, India - Ahmed, Minhajuddin; Shah, Kuldeep; Kshirsagar, Vinayak Yadavrao (International Journal of Contemporary Pediatrics, 2016)
Background: Obesity is defined as the abnormal growth of adipose tissue due to enlargement of fat cells size or increase in their number or a combination of both. The aim was to find out the prevalence of obesity in school going children aged between 10-14 years in urban and rural areas of Karad, Maharashtra, India and to compare its prevalence of obesity with its risk factor. Methods: A cross sectional randomized study of 360 children from schools in urban and rural areas of Karad, Maharashtra, India was conducted to find out the prevalence of obesity.181 children from urban school and 179 from rural school were included. Results:The prevalence of overweight and obesity in urban area is 6.6% and 2.2%. The prevalence of overweight and obesity in rural area is 3.4% and 0.6%. Risk factors in urban area were male sex, television viewing >1 hour, transport to school, family history of obesity and diabetes. Conclusions:The prevalence of overweight/obesity is higher in urban area compared to rural area. Lack of physical activity and family factors are important risk factors.